THE RELATIONSHIP BETWEEN VISCERAL FAT AND RISK OF OBSTRUCTIVE SLEEP APNEA IN MEDICAL STUDENTS - Muhammad Ferrel Privansyah Cader Cader; Nurfitri Bustamam; Feda Anisah Makkiyah; Marlina Dewiastuti (Fakultas Kedokteran Universitas Sriwijaya, 2024)
The COVID-19 pandemic has caused changes in student’s lifestyles, triggering visceral fat accumulation. Visceral fat accumulation increases the risk of obstructive sleep apnea because it causes airway collapse. This study aims to determine the relationship between visceral fat and the risk level of obstructive sleep apnea in medical students. The study used a cross-sectional design on 55 students from the Faculty of Medicine, Universitas Pembangunan Nasional Veteran Jakarta, using a simple random sampling technique. Visceral fat was measured using the Tanita Body Composition analyzer, while the obstructive sleep apnea risk level was measured using the stop-bang questionnaire. The body mass index differed between the normal and high visceral fat groups (p=0.000). There were no differences in age, sedentary behavior, and eating habits between visceral fat groups (p > 0.05). Chi-square exact test results showed a relationship between visceral fat and the risk level of obstructive sleep apnea (p = 0.018). The higher the visceral fat, the higher the risk level of obstructive sleep apnea.